Hyponatraemia despite isotonic maintenance fluid therapy: a time series intervention study. Issue 5 (28th October 2020) - Chromek, Milan; Jungner, Åsa; Rudolfson, Niclas; Ley, David; Bockenhauer, Detlef; Hagander, Lars
Abstract : Objective: To examine the prevalence of dysnatraemias among children admitted for paediatric surgery before and after a change from hypotonic to isotonic intravenous maintenance fluid therapy. Design: Retrospective consecutive time series intervention study. Setting: Paediatric surgery ward at the Children's Hospital in Lund, during a 7-year period, 2010–2017. Patients: All children with a blood sodium concentration measurement during the study period were included. Hypotonic maintenance fluid (40 mmol/L NaCl and 20 mmol/L KCl) was used during the first 3 years of the study (646 patients), and isotonic solution (140 mmol/L NaCl and 20 mmol/L KCl) was used during the following period (807 patients). Main outcome measures: Primary outcomes were sodium concentration and occurrence of hyponatraemia (<135 mmol/L) or hypernatraemia (>145 mmol/L). Results: Overall, the change from hypotonic to isotonic intravenous maintenance fluid therapy was associated with a decreased prevalence of hyponatraemia from 29% to 22% (adjusted OR 0.65 (0.51–0.82)) without a significantly increased odds for hypernatraemia (from 3.4% to 4.3%, adjusted OR 1.2 (0.71–2.1)). Hyponatraemia <130 mmol/L decreased from 6.2% to 2.6%, and hyponatraemia <125 mmol/L decreased from 2.0% to 0.5%. Conclusions: Routine use of intravenous isotonic maintenance fluids was associated with lower prevalence of hyponatraemia, although hyponatraemia still occurred in over 20% of patients. We propose that the composition and the volume of administered fluid need to be addressed.